Molecular genetic analysis of the strain Leningrad-16 used for the production of measles vaccine - Georgy M. Ignatyev; Alena V. Atrasheuskaya; Lidiya L. Sukhanova; Elena S. Sidorenko; Nina A. Netesova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2020)
Aim. To study the genetic stability of the measles virus strain Leningrad-16 (L-16) used for the production of vaccine at JSC NPO Mikrogen.Materials and methods. A series of production and sowing strains of L-16 (JSC NPO Mikrogen), ready-made series of measles vaccines from various manufacturers, and the strain of measles virus genotype D6 were studied. Molecular genetic study of the strains was performed using RT-PCR followed by restriction analysis and sequencing.Results. The complete genome sequences of the production and sowing strains of L-16 that are used for vaccine production were obtained. The sequence of the vaccine strain was deposited in GenBank. Strain L-16 was confirmed to be genetically stable. The obtained data demonstrated the possibility of using the RT-PCR method with subsequent restriction analysis to confirm the authenticity of the vaccine strain L-16 in finished mono and three component vaccines.Conclusion. The results of the study suggest the applicability of the molecular genetic methods to confirm the authenticity of the studied strains not only at the production stages, but also in the finished series of vaccines.